2003
DOI: 10.1038/sj.onc.1206120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tyrosine kinase inhibitor STI571 on the kinase activity of wild-type and various mutated c-kit receptors found in mast cell neoplasms

Abstract: Systemic mastocytosis (SM) is a rare disease caused by an abnormal mast cell accumulation in various tissues. Two classes of constitutive activating c-kit mutations are found in SM. The most frequent class occurs in the catalytic pocket coding region with substitutions at codon 816 and the other in the intracellular juxtamembrane coding region. Therefore, kinase inhibitors that block mutated c-kit activity might be used as therapeutic agents in SM. Here, we show that STI571 inhibits both wild-type and juxtamem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(123 citation statements)
references
References 26 publications
8
112
0
3
Order By: Relevance
“…This may reflect some mechanistic or signaling differences not only between WT receptor activation and mutated receptor activation but also between two types of mutations. Interestingly, in this report we showed that JMD receptor appeared to be more sensitive to compounds reported to be active on the WT receptor, whereas these drugs are ineffective when assessed on KIT m814/h816 -mutated expressing cells (Ning et al, 2001;Frost et al, 2002;Zermati et al, 2003). These data are very encouraging in the perspective of treating GISTs with STi-571.…”
Section: Difference In Receptor Features Between Wt and Kit Jmd Mutatsupporting
confidence: 70%
“…This may reflect some mechanistic or signaling differences not only between WT receptor activation and mutated receptor activation but also between two types of mutations. Interestingly, in this report we showed that JMD receptor appeared to be more sensitive to compounds reported to be active on the WT receptor, whereas these drugs are ineffective when assessed on KIT m814/h816 -mutated expressing cells (Ning et al, 2001;Frost et al, 2002;Zermati et al, 2003). These data are very encouraging in the perspective of treating GISTs with STi-571.…”
Section: Difference In Receptor Features Between Wt and Kit Jmd Mutatsupporting
confidence: 70%
“…Demonstrates in vitro efficacy against wild-type KIT and certain transmembrane (F522C) and juxta-membrane (V560G) KIT mutants, but not the common kinase (D816V) domain mutants [45,[105][106][107]. Similarly, not all juxta-membrane mutations may be sensitive to IM (e.g., V559I) [108].…”
Section: Imatinib Mesylate (Im)mentioning
confidence: 99%
“…A syndrome related to histamine release may also occur. Imatinib inhibition of KIT phosphorylation in mast cell lines correlates with the inhibition of cellular proliferation (Zermati et al, 2003), suggesting that the cells are critically dependent on KIT activity. In systemic mastocytosis, the most common activating mutation in C-KIT D816V, occurs in the catalytic region of the enzyme, and also prevents binding of imatinib.…”
Section: Other Myeloid Disordersmentioning
confidence: 99%
“…Most cases of mastocytosis are therefore resistant to imatinib. However, patients with mutations in the juxtamembrane region of the KIT molecule may retain in vitro sensitivity (Zermati et al, 2003) and durable clinical responses to imatinib in doses of 400 mg daily or less have been demonstrated .…”
Section: Other Myeloid Disordersmentioning
confidence: 99%
See 1 more Smart Citation